Provocative Information Flows on TikTok During Disaster Events in Sibolga, Padang, and Aceh: A Netnographic Study from the Perspective of Digital Communication - Sabena Sabena (Baca Dulu Publisher, 2026)
The rise of provocative content related to natural disasters on TikTok over the past five years indicates a significant shift in people's information consumption patterns. This study aims to analyze how netizens construct, respond to, and interpret this content, particularly in the cases of floods and flash floods in Sibolga, Padang, and Aceh. Using a constructivist paradigm, this study adopted a qualitative approach with a netnography method that focuses on the dynamics of digital interactions on TikTok. Data were collected through online observation, content downloads, comment interactions, and visual-narrative analysis. All data were then coded using NVivo 12 Plus software to identify thematic patterns.The research findings reveal three main findings. First, provocative content on TikTok is constructed through dramatic narratives, the use of visual effects, and the choice of emotional diction that reinforces the sense of threat. Second, netizen responses shape the negotiation of meaning through three patterns: amplification of fear, clarification based on local experience, and critical reframing. Third, the spread of unverified information is fueled by low digital literacy, the speed of TikTok information circulation, and the lack of intervention from authoritative actors in providing prompt clarification. This research confirms that TikTok acts as a discursive space that influences public perception of disasters, thus requiring strengthening disaster communication strategies through collaboration between the government, media, and digital communities. These findings provide theoretical contributions to the study of disaster communication and social media, and offer practical recommendations for limiting the escalation of provocative messages on digital platforms.